Exploration work function and optical properties of monolayer SnSe allotropes - Cui, Zhen; Wang, Xia; Ding, Yingchun; Li, Meiqin (Superlattices and microstructures, 2018)
The work function and optical properties are investigated with density functional theory for three monolayer SnSe allotropes. The calculated results indicate that the α-SnSe, δ-SnSe, ε-SnSe are semiconductor with the band gaps of 0.90, 1.25, and 1.50 eV, respectively. Meanwhile, the work function of δ-SnSe is lower than α-SnSe and ε-SnSe, which indicates that the δ-SnSe can be prepared of photoemission and field emission nanodevices. More importantly, the α-SnSe, δ-SnSe, ε-SnSe with the large static dielectric constants are 4.22, 5.48, and 3.61, which demonstrate that the three monolayer SnSe allotropes can be fabricated the capacitor. In addition, the static refractive index of δ-SnSe is larger than α-SnSe and ε-SnSe. The different optical properties with three monolayer SnSe allotropes reveal that the allotropes can regulate the properties of the materials. Moreover, our researched results show that the three monolayer SnSe allotropes are sufficient for fabrication of optoelectronic nanodevices. [Display omitted] •The work function and optical properties are investigated with density functional theory for three monolayer SnSe allotropes.•The α-SnSe, δ-SnSe, ε-SnSe are semiconductor with the band gaps of 0.90, 1.25, and 1.50 eV.•The work function of δ-SnSe is lower than many other 2D materials.•The three monolayer SnSe allotropes can be fabricated the capacitor.